A lightweight flame-retardant epoxy casting material composition for capacitors and preparation method thereof

By adding modified core-shell rubber particles and other lightweight fillers to epoxy castables for capacitors, the problem of insufficient performance of epoxy castables in high-temperature and high-pressure environments has been solved, and low density, high flame retardancy and good performance have been achieved. mechanical properties.

CN118620351BActive Publication Date: 2025-01-24SICHUAN PROVINCE SCI CITY JIUXIN SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410736998.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-01-24
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

The existing epoxy castables for capacitors have shortcomings in their impact resistance, crack resistance, density, high temperature resistance and flame retardancy, and cannot meet the requirements of high temperature and high pressure extreme environments.

Method used

A light flame -retardant epoxy pouring composition is used, and the nuclear shell rubber particle modifiers are added to the epoxy resin. The modified composition includes epoxy resin, nuclear shell rubber particle modifiers, fillers, and filling Components such as flame retardants and curing agents improve the comprehensive performance of materials by complexity and modification.

Benefits of technology

The low density, high flame retardability, good thermal conductivity and mechanical strength of epoxy pouring materials can maintain stability in high temperature and high -pressure environment, and improve the energy storage efficiency and safety performance of capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118620351B_ABST
    Figure CN118620351B_ABST
Patent Text Reader

Abstract

The present invention discloses a lightweight flame-retardant epoxy casting material composition for capacitors and a preparation method thereof, which belongs to the field of capacitor manufacturing, and includes component A and component B; component A includes the following components: epoxy resin, epoxy resin modifier, epoxy diluent, filler, pigment, flame retardant, coupling agent; component B includes the following components: curing agent, accelerator; the epoxy resin modifier is a toughening modifier. The present invention modifies epoxy resin by epoxy resin modifier, effectively improving the impact resistance and cracking resistance of the material, so that the capacitor has better reliability under extreme high-voltage environment; at the same time, each component in the filler of the present invention is a lightweight filler, and the use of lightweight filler reduces the weight of the capacitor itself, which helps to improve the energy storage efficiency of the capacitor; in addition, the present invention adopts a special halogen-free flame retardant for epoxy resin, which not only meets the requirements of capacitors in terms of safety performance, but also follows the development trend of green environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of capacitor manufacturing and relates to a lightweight flame-retardant epoxy casting material composition for capacitors and a preparation method thereof. Background Art

[0002] In the capacitor industry, with the growing demand for high-performance capacitors in new energy, electronic equipment and other fields, improving the comprehensive performance of capacitor materials has become a key research and development direction.

[0003] Commonly used epoxy castables for capacitors are mainly composed of epoxy resins, which have deficiencies in impact resistance, crack resistance, density, high temperature resistance and flame retardancy. During the working process of capacitors, they often face extreme environments such as high temperature and high pressure. Commonly used epoxy castables for capacitors cannot meet the use of capacitors in extreme environments of high temperature and high pressure. Therefore, toughened modified epoxy resins are currently used as the main component for the preparation of epoxy castables for capacitors. Toughened modified epoxy resins can improve the brittleness of epoxy resins to a certain extent, reduce internal stress, and improve the crack resistance of epoxy cured products, making epoxy castables for capacitors suitable for high-voltage environments.

[0004] At present, the brittleness and crack resistance of epoxy resin cured products are mainly improved by adding terminal carboxyl nitrile rubber, core-shell structure rubber, core-shell structure rubber particles, polyurethane toughening agents and other materials. Reference patent CN202410152337.8 A kind of epoxy casting material composition for power capacitors and its preparation method.

[0005] The modified effect of core-shell rubber is remarkable. The epoxy casting material modified by core-shell rubber can be used in high-pressure environment. The modification principle of core-shell rubber is mainly realized through its unique structure. The core-shell rubber particles are composed of a core and an outer shell, both of which are composed of different polymer components. Specifically, the core is usually a softer rubber material, such as styrene-butadiene rubber or polybutadiene rubber, while the outer shell is a harder plastic material, such as polymethyl methacrylate (PMMA).

[0006] During the toughening process, the shell layer swells in the epoxy resin to form an interpenetrating network, which significantly increases the viscosity of the system, thereby improving the overall performance of the material. In addition, the high crosslinking density or functional groups of the shell layer are not conducive to toughening because these factors affect the mechanical properties of the material.

[0007] The core acts as a stress concentrator, which can induce silver streaks and shear bands to absorb energy, and can also terminate silver streaks, thereby effectively absorbing and dispersing the stress generated by external impact. This structural design enables the core-shell rubber particles to eliminate stress in the solidified material system when subjected to external forces, thereby playing a toughening role.

[0008] In summary, the toughening principle of core-shell rubber particles mainly relies on the synergistic effect of its core and shell: the core improves the impact toughness of the material by absorbing and dispersing stress, while the shell increases the viscosity and overall performance of the material by interacting with the epoxy resin. This structural optimization can significantly improve the comprehensive mechanical properties of the material.

[0009] The toughening effect of core-shell structure rubber is very good, but at high temperature, the core and shell of the core-shell structure rubber will separate. The reasons for the separation of the two mainly include the following points: there are interfacial stresses between the core and the shell. Under high temperature environment, these stresses may increase due to the mismatch of thermal expansion coefficients of the materials, resulting in interface cracking or separation; there are cross-linking points between the molecular chains of the rubber, and these cross-linking points may break at high temperatures, causing changes in the physical properties of the rubber. When the cross-linking point breaks at the interface between the core and the shell, separation occurs; rubber is susceptible to oxidation at high temperatures, resulting in aging, hardening or embrittlement of the material. This change may make the connection between the core and the shell fragile and separate.

[0010] In addition, the density of capacitors is relatively high, which affects their energy storage efficiency, and the low flame retardant performance also limits their application in situations with high safety requirements. Therefore, researching and developing a high-quality epoxy casting material composition with excellent impact resistance, crack resistance, low density and high flame retardant performance is of great significance to improving the comprehensive performance of capacitors. Summary of the invention

[0011] The purpose of the present invention is to provide a lightweight flame-retardant epoxy castable composition for capacitors and a preparation method thereof, which solves the problem that the commonly used epoxy castables for capacitors are mainly composed of epoxy resins, and the epoxy resin cured product has high brittleness and low impact resistance. During the working process of the capacitor, the commonly used epoxy castables for capacitors have deficiencies in impact resistance, crack resistance, density, high temperature resistance and flame retardancy.

[0012] The technical solution adopted by the present invention is as follows:

[0013] A lightweight flame-retardant epoxy casting material composition for capacitors, comprising component A and component B;

[0014] The component A comprises the following components: epoxy resin, epoxy resin modifier, epoxy diluent, filler, pigment, flame retardant, coupling agent;

[0015] The component B includes the following components: a curing agent and an accelerator;

[0016] The epoxy resin includes bisphenol A epoxy resin E51 and bisphenol A epoxy resin E44, wherein the mass ratio of bisphenol A epoxy resin E51 to bisphenol A epoxy resin E44 is 1:1.5;

[0017] The epoxy diluent includes phenyl glycidyl ether and neopentyl glycol diglycidyl ether, the mass ratio of phenyl glycidyl ether to neopentyl glycol diglycidyl ether is 2:1, and the amount of epoxy diluent added is 17-18% of the total mass of the epoxy resin;

[0018] The filler comprises the following components: active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, thermal conductive aluminum oxide powder, and the density of the thermal conductive aluminum oxide powder is 3.0-3.5 g / cm 3 , fineness is 800 mesh, density of hollow glass beads is 0.2-0.3g / cm 3 , hollow ceramic microspheres 0.75-0.90g / cm 3 ; The mass ratio of active silicon powder 1250 mesh, hollow glass beads, hollow coal slag powder, hollow ceramic microspheres, and thermal conductive aluminum oxide powder is 1:2:1:2:1, and the mass of the filler is 80% of the total mass of the epoxy resin;

[0019] The flame retardant is a halogen-free flame retardant specially used for epoxy resin, and the amount of the flame retardant added is 20% of the total mass of the epoxy resin;

[0020] The coupling agent is one or more of coupling agent KH570, coupling agent KH560, and titanate coupling agent, and the amount of the coupling agent added is 1.5% of the total mass of the epoxy resin;

[0021] The curing agent is anhydride, and the amount of anhydride added is 30%-40% of the total mass of component A;

[0022] The accelerator is composed of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol, wherein the mass ratio of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol is 1:1:2:1:2, and the amount of the accelerator added is 0.6%-1.5% of the mass of the curing agent;

[0023] The epoxy resin modifier is a toughening modifier.

[0024] The present invention modifies epoxy resin by using epoxy resin modifier, thereby effectively improving the impact resistance and crack resistance of the material, so that the capacitor has better reliability under extreme high-voltage environment; at the same time, each component in the filler of the present invention is a lightweight filler, and the use of lightweight fillers reduces the weight of the capacitor itself, which helps to improve the energy storage efficiency of the capacitor; in addition, the present invention uses a special halogen-free flame retardant for epoxy resin, which not only meets the safety performance requirements of the capacitor, but also follows the development trend of green environmental protection.

[0025] The filler of the present invention uses hollow material as the main component, and is combined with active silicon micropowder and thermal conductive aluminum oxide powder. It not only has the performance of low casting density and light casting body, but also has good thermal conductivity and high mechanical strength.

[0026] After epoxy resin modifiers are used to toughen epoxy resin, although the toughness of epoxy resin is significantly improved, the tensile strength, mechanical strength and other properties of epoxy resin will also be reduced. For example, when adding polyurethane toughening agents, when the addition amount exceeds a certain amount (such as 15%), the tensile strength of the modified material may begin to gradually decrease. This is because excessive toughening agents cause the modified material, which is already close to saturation, to have an anti-synergistic effect, affecting the tensile strength of the modified material; but if the addition amount is too small, no significant toughening effect can be achieved. In addition, when the compatibility of the modifier and the epoxy resin matrix is ​​poor, the modifier may not be evenly dispersed in the epoxy resin, forming a multiphase structure. This structure is prone to uneven stress distribution when subjected to external forces, causing some performance degradation. For example, when rubber toughens epoxy resin, if the compatibility of rubber and epoxy resin is poor, the interfacial bonding force between the rubber phase and the epoxy resin phase may be weakened, thereby affecting the overall performance.

[0027] Therefore, in order to ensure that the comprehensive performance of the lightweight flame-retardant epoxy castable is good, the present invention compounds a plurality of components, utilizes the advantages of each component itself, and combines the chemical and physical reactions generated between the corresponding components. By using the component A and the component B in combination, the castable obtained has a small density after curing, a light castable body, good toughness, high impact strength, good resistance to cold and hot shocks, excellent electrical properties, and high mechanical strength. The problem that the commonly used epoxy castable for capacitors is mainly composed of epoxy resin as the main component and the epoxy resin cured product has high brittleness and low impact resistance, and in the working process of the capacitor, the commonly used epoxy castable for capacitors has deficiencies in impact resistance, crack resistance, density, high temperature resistance, flame retardancy, etc.

[0028] Further, the epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 20-30 parts of core-shell rubber particle modifier;

[0029] The shell of the core-shell rubber particle is a polymethyl methacrylate shell with uniformly distributed pores, and the core of the core-shell rubber particle is an amino-based bio-based itaconate-butadiene rubber;

[0030] The core-shell rubber particle modifier comprises the following components in parts by weight: 20-30 parts of dibutyltin dilaurate, 80-90 parts of trimethylsilyl isocyanate, 10-15 parts of nano-activated carbon, and 40-50 parts of polyvinyl chloride.

[0031] Further, the core-shell rubber particle modifier comprises the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 40 parts of polyvinyl chloride;

[0032] The epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 25 parts of core-shell rubber particle modifier.

[0033] Furthermore, the epoxy resin modifier is prepared by the following method:

[0034] A. Preparation of core-shell rubber particle modifier

[0035] The core-shell rubber particle modifier is prepared by the following method: polyvinyl chloride is molten in a container at 100° C., trimethylsilyl isocyanate and nano-activated carbon are added to the polyvinyl chloride, and the mixture is stirred uniformly at 100° C. to obtain a glue solution, and dibutyltin dilaurate is added to the glue solution after the mixture is cooled to 40-50° C., and the mixture is stirred uniformly to obtain a shell rubber particle modifier;

[0036] B. Preparation of core-shell rubber particles

[0037] The method for preparing the core-shell rubber particles comprises the following steps:

[0038] B1. Kernel Preparation

[0039] Bio-based itaconate is prepared from bio-based monomers itaconic acid and isopentanol by esterification reaction, and then by emulsion polymerization, a vinyl-containing silane modifier, deionized water, bio-based itaconate, butadiene and a redox initiator are mixed at 60-80°C in an inert atmosphere to form an emulsion; then, the bio-based itaconate is copolymerized with butadiene in the emulsion state to generate bio-based itaconate-butadiene rubber, wherein the mass ratio of bio-based itaconate to butadiene is 3:2, the copolymerization temperature is 75-85°C, and the reaction time is 7-8 hours; the generated bio-based itaconate-butadiene rubber is subjected to an amination reaction with an amination agent to obtain an amination bio-based itaconate-butadiene rubber;

[0040] B2. Shell Preparation

[0041] The invention adopts an emulsion polymerization method, uses ammonium persulfate as an initiator, and OP-10 as an emulsifier, and at 70° C., methyl methacrylate is mixed with ammonium persulfate, OP-10, and deionized water for emulsion polymerization to obtain a PMMA latex particle solution; N,N-dimethylformamide is added to the PMMA latex particle solution, and the mixed solution is fully stirred under ultrasonic wave to ensure that N,N-dimethylformamide is uniformly dispersed in the PMMA latex particles, so as to obtain a mixed solution containing PMMA latex particles; and the mixed solution containing the PMMA latex particles is placed at room temperature, and N,N-dimethylformamide is naturally volatilized. As the solvent is volatilized, the solvent in the PMMA latex particles is removed to form a pore structure, so as to obtain polymethyl methacrylate latex particles with uniformly distributed pores;

[0042] B3. Core-shell structure formation

[0043] The prepared aminated bio-based itaconate-butadiene rubber particles are used as seed particles and dispersed in a suitable solvent to form a stable seed particle dispersion; polymethyl methacrylate latex particles with uniform pores are mixed with the seed latex particle dispersion to ensure that the two particles are fully in contact, and then azobisisobutyronitrile is added to carry out a grafting reaction between the polymethyl methacrylate latex particles with uniform pores and the aminated bio-based itaconate-butadiene rubber particles at 80-100° C. After the grafting reaction is completed, the product is separated, washed and dried to obtain aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure, wherein the aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure are core-shell rubber particles;

[0044] C. Modification of core-shell rubber particles

[0045] A shell rubber particle modifier is sprayed onto the core-shell rubber particles with a high-pressure spray gun. The shell rubber particle modifier penetrates into the pores of the outer shell of the core-shell rubber particles under the action of high pressure. Part of the shell rubber particle modifier is filled in the pores of the outer shell of the core-shell rubber particles. Part of the shell rubber particle modifier acts on the inner core through the pores of the outer shell of the core-shell rubber particles to complete the modification of the core-shell rubber particles, thereby obtaining shell rubber particles modified by the core-shell rubber particle modifier, wherein the modified shell rubber particles are epoxy resin modifiers.

[0046] The present invention modifies the shell rubber particles, solving the problem of using core-shell structure rubber to modify epoxy resin in the existing epoxy casting material for capacitors. Although the compression and impact resistance of the epoxy casting material for capacitors are enhanced and it can be used in extreme high-voltage environments, the existing core-shell structure rubber has the phenomenon of separation of the inner core and the outer shell at high temperatures, resulting in the problem that the epoxy casting material for capacitors modified with the core-shell structure rubber cannot be stably applied to extreme high-temperature environments.

[0047] The modification principle of the present invention is as follows: the present invention first performs pore-forming treatment on the outer shell to improve the porosity of the outer shell, so as to facilitate the modification and embedding into the outer shell and react with the inner core; in the present invention, dibutyltin dilaurate is a catalyst, trimethylsilyl isocyanate is a main component, nano-activated carbon is used as a filler and the physical adsorption between the modifier and the inner core and the outer shell is enhanced, and polyvinyl chloride is used as a carrier, which has good fluidity and film-forming property; at room temperature or low temperature, trimethylsilyl isocyanate is combined with nano-activated carbon, polyvinyl chloride and dibutyltin dilaurate through physical adsorption and is filled in the gap of the outer shell; based on the film-forming effect of polyvinyl chloride, at low temperature or room temperature, the modifier is a solid structure filled in the gap of the outer shell, which can not only keep The outer shaping of the shell does not reduce the adhesion between the rubber particles and the matrix resin, and thus does not affect the toughening effect; when the capacitor is used in a high temperature environment, the high temperature environment is above 120°C, the polyvinyl chloride becomes a molten state, and trimethylsilyl isocyanate and dibutyl tin dilaurate are released. At 120°C and under the catalytic action of dibutyl tin dilaurate as a catalyst, the trimethylsilyl isocyanate will chemically react with the polymethyl methacrylate in the shell and the amino bio-based itaconate-butadiene in the core at the same time. The present invention uses trimethylsilyl isocyanate as an intermediate bridge to strengthen the connection strength between the core and the shell, and effectively avoids the separation of the core and the shell under high temperature conditions.

[0048] With dibutyltin dilaurate as a catalyst, the reaction mechanism of trimethylsilyl isocyanate and polymethyl methacrylate at 120°C is as follows: During the reaction, the tin atom of dibutyltin dilaurate forms a coordination bond with the nitrogen atom of isocyanate, thereby activating the isocyanate group and making it easier to react. The isocyanate group (-NCO) of trimethylsilyl isocyanate is activated under the catalytic action of dibutyltin dilaurate, and the activated isocyanate group reacts chemically with the hydroxyl group (-OH) and amino group (-NH2) in polymethyl methacrylate to form a reaction site. As the reaction continues, the isocyanate group combines with the reaction site in polymethyl methacrylate to form a stable cross-linking structure.

[0049] The reaction mechanism of trimethylsilyl isocyanate and amino-based itaconate-butadiene rubber at 120°C with dibutyltin dilaurate as catalyst is as follows: amino-based itaconate-butadiene is a bio-based polymer compound containing amino groups (-NH2). As a nucleophilic reagent, the amino group (-NH2) is easy to react with the isocyanate group. As a nucleophilic reagent, the amino group (-NH2) attacks the electrophilic carbon atom of the isocyanate group (-NCO) to form an intermediate product. Under the action of the catalyst and a high temperature of 120°C, the intermediate product undergoes intramolecular rearrangement accompanied by elimination reactions, such as the elimination of the silyl group, to form a more stable carbamate compound structure.

[0050] In addition, dibutyltin dilaurate not only has a catalytic effect as a catalyst, but also can be used as a stabilizer for polyvinyl chloride, and can capture free radicals generated during the degradation of PVC to prevent the continuation of the chain reaction. In addition, under the action of the catalyst and high temperature, trimethylsilyl isocyanate reacts with unstable sites (such as double bonds, chlorine atoms, etc.) on the polyvinyl chloride chain to form stable chemical bonds, thereby further improving the stability of PVC. The polyvinyl chloride in the present invention serves as a carrier of the modifier, and under the action of dibutyltin dilaurate and trimethylsilyl isocyanate, the performance is stable and suitable for high temperature environments.

[0051] In summary, with dibutyltin dilaurate as a catalyst, at a temperature of 120°C, trimethylsilyl isocyanate, polymethyl methacrylate, and amino-modified bio-based itaconate-butadiene rubber can react chemically at the same time to generate a stable compound structure. Combined with the embedded connection between the modifier and the shell, the modifier can act as a bridge to strengthen the connection strength between the shell and the core at temperatures of 120°C and above.

[0052] Furthermore, the epoxy resin-specific halogen-free flame retardant is 9,10-dioxa-9,10-diaza-1,3,5,7-pentafluoro-2H-pyrrole-2-one.

[0053] Furthermore, the acid anhydride includes methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, the mass ratio of methyltetrahydrophthalic anhydride to methylhexahydrophthalic anhydride is 3:2, and the amount of acid anhydride added is 35% of the total mass of component A.

[0054] Furthermore, the coupling agent is coupling agent KH570 and coupling agent KH560, and the mass ratio of coupling agent KH570 to coupling agent KH560 is 1:1.

[0055] Furthermore, the component A also includes a leveling agent, a defoamer, and a dispersant for epoxy resin. The leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant. The added amount of the leveling agent, the defoamer, and the dispersant is 1.5% of the total mass of component A.

[0056] The method for preparing a lightweight flame-retardant epoxy casting material composition for capacitors comprises the following steps:

[0057] S1. Add filler and coupling agent to a vacuum mixer, treat at 80-85°C for 1.5-2.0 hours, then add epoxy resin, epoxy diluent, epoxy resin modifier, pigment and flame retardant to the vacuum mixer, then disperse at high speed at 85-90°C and -0.06--0.08MPa vacuum for 1.0-1.5 hours, filter the material to obtain component A;

[0058] S2. Add anhydride and accelerator into a reaction kettle, and stir at 75-85° C. for 1.0-2.0 hours to obtain component B;

[0059] S3. When in use, preheat components A and B to 70-80°C respectively, and then mix them evenly to obtain a lightweight flame-retardant epoxy casting material composition for capacitors.

[0060] Furthermore, the epoxy resin modifier in step S1 is prepared by the following method:

[0061] A. Preparation of core-shell rubber particle modifier

[0062] The core-shell rubber particle modifier is prepared by the following method: polyvinyl chloride is molten in a container at 100° C., trimethylsilyl isocyanate and nano-activated carbon are added to the polyvinyl chloride, and the mixture is stirred uniformly at 100° C. to obtain a glue solution, and dibutyltin dilaurate is added to the glue solution after the mixture is cooled to 40-50° C., and the mixture is stirred uniformly to obtain a shell rubber particle modifier;

[0063] B. Preparation of core-shell rubber particles

[0064] The method for preparing the core-shell rubber particles comprises the following steps:

[0065] B1. Kernel Preparation

[0066] Bio-based itaconate is prepared from bio-based monomers itaconic acid and isopentanol by esterification reaction, and then by emulsion polymerization, a vinyl-containing silane modifier, deionized water, bio-based itaconate, butadiene and a redox initiator are mixed at 60-80°C in an inert atmosphere to form an emulsion; then, the bio-based itaconate is copolymerized with butadiene in the emulsion state to generate bio-based itaconate-butadiene rubber, wherein the mass ratio of bio-based itaconate to butadiene is 3:2, the copolymerization temperature is 75-85°C, and the reaction time is 7-8 hours; the generated bio-based itaconate-butadiene rubber is subjected to an amination reaction with an amination agent to obtain an amination bio-based itaconate-butadiene rubber;

[0067] B2. Shell Preparation

[0068] The invention adopts an emulsion polymerization method, uses ammonium persulfate as an initiator, and OP-10 as an emulsifier, and at 70° C., methyl methacrylate is mixed with ammonium persulfate, OP-10, and deionized water for emulsion polymerization to obtain a PMMA latex particle solution; N,N-dimethylformamide is added to the PMMA latex particle solution, and the mixed solution is fully stirred under ultrasonic wave to ensure that N,N-dimethylformamide is uniformly dispersed in the PMMA latex particles, so as to obtain a mixed solution containing PMMA latex particles; and the mixed solution containing the PMMA latex particles is placed at room temperature, and N,N-dimethylformamide is naturally volatilized. As the solvent is volatilized, the solvent in the PMMA latex particles is removed to form a pore structure, so as to obtain polymethyl methacrylate latex particles with uniformly distributed pores;

[0069] B3. Core-shell structure formation

[0070] The prepared aminated bio-based itaconate-butadiene rubber particles are used as seed particles and dispersed in a suitable solvent to form a stable seed particle dispersion; polymethyl methacrylate latex particles with uniform pores are mixed with the seed latex particle dispersion to ensure that the two particles are fully in contact, and then azobisisobutyronitrile is added to carry out a grafting reaction between the polymethyl methacrylate latex particles with uniform pores and the aminated bio-based itaconate-butadiene rubber particles at 80-100° C. After the grafting reaction is completed, the product is separated, washed and dried to obtain aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure, wherein the aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure are core-shell rubber particles;

[0071] C. Modification of core-shell rubber particles

[0072] A shell rubber particle modifier is sprayed onto the core-shell rubber particles with a high-pressure spray gun. The shell rubber particle modifier penetrates into the pores of the outer shell of the core-shell rubber particles under the action of high pressure. Part of the shell rubber particle modifier is filled in the pores of the outer shell of the core-shell rubber particles. Part of the shell rubber particle modifier acts on the inner core through the pores of the outer shell of the core-shell rubber particles to complete the modification of the core-shell rubber particles, thereby obtaining shell rubber particles modified by the core-shell rubber particle modifier, wherein the modified shell rubber particles are epoxy resin modifiers.

[0073] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0074] 1. The lightweight flame-retardant epoxy castable composition for capacitors of the present invention is compounded with multiple components, utilizing the advantages of each component itself, and combining the chemical and physical reactions generated between the corresponding components. By using component A and component B in combination, the castable obtained has low density after curing, light castable mass, good toughness, high impact strength, good cold and hot shock resistance, excellent electrical properties, and high mechanical strength. It solves the problem that the commonly used epoxy castable for capacitors is mainly composed of epoxy resin as the main component, and the epoxy resin cured product has high brittleness and low impact resistance. During the working process of the capacitor, the commonly used epoxy castable for capacitors has deficiencies in impact resistance, crack resistance, density, high temperature resistance and flame retardancy;

[0075] 2. The method for preparing a lightweight flame-retardant epoxy casting material composition for capacitors of the present invention modifies the core-shell rubber particles, thereby solving the problem of core-shell separation of the core-shell rubber particles at high temperatures of 120° C. or above. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work, among which:

[0077] Figure 1 This is a microscopic image of the impact interface of the cured lightweight flame-retardant epoxy castable of Example 1 under an impact force of 25KJ;

[0078] Figure 2 This is a microscopic image of the impact interface of the lightweight flame retardant epoxy castable cured product of the present invention in Comparative Example 1 under an impact force of 25KJ. DETAILED DESCRIPTION

[0079] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.

[0080] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0081] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0082] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0083] A lightweight flame-retardant epoxy casting material composition for capacitors, comprising component A and component B;

[0084] The component A comprises the following components: epoxy resin, epoxy resin modifier, epoxy diluent, filler, pigment, flame retardant, coupling agent;

[0085] The component B includes the following components: a curing agent and an accelerator;

[0086] The epoxy resin includes bisphenol A epoxy resin E51 and bisphenol A epoxy resin E44, wherein the mass ratio of bisphenol A epoxy resin E51 to bisphenol A epoxy resin E44 is 1:1.5;

[0087] The epoxy diluent includes phenyl glycidyl ether and neopentyl glycol diglycidyl ether, the mass ratio of phenyl glycidyl ether to neopentyl glycol diglycidyl ether is 2:1, and the amount of epoxy diluent added is 17-18% of the total mass of the epoxy resin;

[0088] The filler comprises the following components: active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, thermal conductive aluminum oxide powder, and the density of the thermal conductive aluminum oxide powder is 3.0-3.5g / cm 3 , fineness is 800 mesh, density of hollow glass beads is 0.2-0.3g / cm 3 , hollow ceramic microspheres 0.75-0.90g / cm 3 ; The mass ratio of active silicon powder 1250 mesh, hollow glass beads, hollow coal slag powder, hollow ceramic microspheres, and thermal conductive aluminum oxide powder is 1:2:1:2:1, and the mass of the filler is 80% of the total mass of the epoxy resin;

[0089] The flame retardant is a halogen-free flame retardant specially used for epoxy resin, and the amount of the flame retardant added is 20% of the total mass of the epoxy resin;

[0090] The coupling agent is one or more of coupling agent KH570, coupling agent KH560, and titanate coupling agent, and the amount of the coupling agent added is 1.5% of the total mass of the epoxy resin;

[0091] The curing agent is anhydride, and the amount of anhydride added is 30%-40% of the total mass of component A;

[0092] The accelerator is composed of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol, wherein the mass ratio of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol is 1:1:2:1:2, and the amount of the accelerator added is 0.6%-1.5% of the mass of the curing agent;

[0093] The epoxy resin modifier is a toughening modifier.

[0094] The present invention modifies epoxy resin by using epoxy resin modifier, thereby effectively improving the impact resistance and crack resistance of the material, so that the capacitor has better reliability under extreme high-voltage environment; at the same time, each component in the filler of the present invention is a lightweight filler, and the use of lightweight fillers reduces the weight of the capacitor itself, which helps to improve the energy storage efficiency of the capacitor; in addition, the present invention uses a special halogen-free flame retardant for epoxy resin, which not only meets the safety performance requirements of the capacitor, but also follows the development trend of green environmental protection.

[0095] The filler of the present invention uses hollow material as the main component, and is combined with active silicon micropowder and thermal conductive aluminum oxide powder. It not only has the performance of low casting density and light casting body, but also has good thermal conductivity and high mechanical strength.

[0096] After epoxy resin modifiers are used to toughen epoxy resin, although the toughness of epoxy resin is significantly improved, the tensile strength, mechanical strength and other properties of epoxy resin will also be reduced. For example, when adding polyurethane toughening agents, when the addition amount exceeds a certain amount (such as 15%), the tensile strength of the modified material may begin to gradually decrease. This is because excessive toughening agents cause the modified material, which is already close to saturation, to have an anti-synergistic effect, affecting the tensile strength of the modified material; but if the addition amount is too small, no significant toughening effect can be achieved. In addition, when the compatibility of the modifier and the epoxy resin matrix is ​​poor, the modifier may not be evenly dispersed in the epoxy resin, forming a multiphase structure. This structure is prone to uneven stress distribution when subjected to external forces, causing some performance degradation. For example, when rubber toughens epoxy resin, if the compatibility of rubber and epoxy resin is poor, the interfacial bonding force between the rubber phase and the epoxy resin phase may be weakened, thereby affecting the overall performance.

[0097] Therefore, in order to ensure that the comprehensive performance of the lightweight flame-retardant epoxy castable is good, the present invention compounds a plurality of components, utilizes the advantages of each component itself, and combines the chemical and physical reactions generated between the corresponding components. By using the component A and the component B in combination, the castable obtained has a small density after curing, a light castable body, good toughness, high impact strength, good resistance to cold and hot shocks, excellent electrical properties, and high mechanical strength. The problem that the commonly used epoxy castable for capacitors is mainly composed of epoxy resin as the main component and the epoxy resin cured product has high brittleness and low impact resistance, and in the working process of the capacitor, the commonly used epoxy castable for capacitors has deficiencies in impact resistance, crack resistance, density, high temperature resistance, flame retardancy, etc.

[0098] Further, the epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 20-30 parts of core-shell rubber particle modifier;

[0099] The shell of the core-shell rubber particle is a polymethyl methacrylate shell with uniformly distributed pores, and the core of the core-shell rubber particle is an amino-based bio-based itaconate-butadiene rubber;

[0100] The core-shell rubber particle modifier comprises the following components in parts by weight: 20-30 parts of dibutyltin dilaurate, 80-90 parts of trimethylsilyl isocyanate, 10-15 parts of nano-activated carbon, and 40-50 parts of polyvinyl chloride.

[0101] Furthermore, the core-shell rubber particle modifier includes the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 40 parts of polyvinyl chloride; the epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 25 parts of core-shell rubber particle modifier.

[0102] Furthermore, the epoxy resin modifier is prepared by the following method:

[0103] A. Preparation of core-shell rubber particle modifier

[0104] The core-shell rubber particle modifier is prepared by the following method: polyvinyl chloride is molten in a container at 100° C., trimethylsilyl isocyanate and nano-activated carbon are added to the polyvinyl chloride, and the mixture is stirred uniformly at 100° C. to obtain a glue solution, and dibutyltin dilaurate is added to the glue solution after the mixture is cooled to 40-50° C., and the mixture is stirred uniformly to obtain a shell rubber particle modifier;

[0105] B. Preparation of core-shell rubber particles

[0106] The method for preparing the core-shell rubber particles comprises the following steps:

[0107] B1. Kernel Preparation

[0108] Bio-based itaconate is prepared from bio-based monomers itaconic acid and isopentanol by esterification reaction, and then by emulsion polymerization, a vinyl-containing silane modifier, deionized water, bio-based itaconate, butadiene and a redox initiator are mixed at 60-80°C in an inert atmosphere to form an emulsion; then, the bio-based itaconate is copolymerized with butadiene in the emulsion state to generate bio-based itaconate-butadiene rubber, wherein the mass ratio of bio-based itaconate to butadiene is 3:2, the copolymerization temperature is 75-85°C, and the reaction time is 7-8 hours; the generated bio-based itaconate-butadiene rubber is subjected to an amination reaction with an amination agent to obtain an amination bio-based itaconate-butadiene rubber;

[0109] B2. Shell Preparation

[0110] The invention adopts an emulsion polymerization method, uses ammonium persulfate as an initiator, and OP-10 as an emulsifier, and at 70° C., methyl methacrylate is mixed with ammonium persulfate, OP-10, and deionized water for emulsion polymerization to obtain a PMMA latex particle solution; N,N-dimethylformamide is added to the PMMA latex particle solution, and the mixed solution is fully stirred under ultrasonic wave to ensure that N,N-dimethylformamide is uniformly dispersed in the PMMA latex particles, so as to obtain a mixed solution containing PMMA latex particles; and the mixed solution containing the PMMA latex particles is placed at room temperature, and N,N-dimethylformamide is naturally volatilized. As the solvent is volatilized, the solvent in the PMMA latex particles is removed to form a pore structure, so as to obtain polymethyl methacrylate latex particles with uniformly distributed pores;

[0111] B3. Core-shell structure formation

[0112] The prepared aminated bio-based itaconate-butadiene rubber particles are used as seed particles and dispersed in a suitable solvent to form a stable seed particle dispersion; polymethyl methacrylate latex particles with uniform pores are mixed with the seed latex particle dispersion to ensure that the two particles are fully in contact, and then azobisisobutyronitrile is added to carry out a grafting reaction between the polymethyl methacrylate latex particles with uniform pores and the aminated bio-based itaconate-butadiene rubber particles at 80-100° C. After the grafting reaction is completed, the product is separated, washed and dried to obtain aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure, wherein the aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure are core-shell rubber particles;

[0113] C. Modification of core-shell rubber particles

[0114] A shell rubber particle modifier is sprayed onto the core-shell rubber particles with a high-pressure spray gun. The shell rubber particle modifier penetrates into the pores of the outer shell of the core-shell rubber particles under the action of high pressure. Part of the shell rubber particle modifier is filled in the pores of the outer shell of the core-shell rubber particles. Part of the shell rubber particle modifier acts on the inner core through the pores of the outer shell of the core-shell rubber particles to complete the modification of the core-shell rubber particles, thereby obtaining shell rubber particles modified by the core-shell rubber particle modifier, wherein the modified shell rubber particles are epoxy resin modifiers.

[0115] The present invention modifies the shell rubber particles, solving the problem of using core-shell structure rubber to modify epoxy resin in the existing epoxy casting material for capacitors. Although the compression and impact resistance of the epoxy casting material for capacitors are enhanced and it can be used in extreme high-voltage environments, the existing core-shell structure rubber has the phenomenon of separation of the inner core and the outer shell at high temperatures, resulting in the problem that the epoxy casting material for capacitors modified with the core-shell structure rubber cannot be stably applied to extreme high-temperature environments.

[0116] The modification principle of the present invention is as follows: the present invention first performs pore-forming treatment on the outer shell to improve the porosity of the outer shell, so as to facilitate the modification and embedding into the outer shell and react with the inner core; in the present invention, dibutyltin dilaurate is a catalyst, trimethylsilyl isocyanate is a main component, nano-activated carbon is used as a filler and the physical adsorption between the modifier and the inner core and the outer shell is enhanced, and polyvinyl chloride is used as a carrier, which has good fluidity and film-forming property; at room temperature or low temperature, trimethylsilyl isocyanate is combined with nano-activated carbon, polyvinyl chloride and dibutyltin dilaurate through physical adsorption and is filled in the gap of the outer shell; based on the film-forming effect of polyvinyl chloride, at low temperature or room temperature, the modifier is a solid structure filled in the gap of the outer shell, which can not only keep The outer shaping of the shell does not reduce the adhesion between the rubber particles and the matrix resin, and thus does not affect the toughening effect; when the capacitor is used in a high temperature environment, the high temperature environment is above 120°C, the polyvinyl chloride becomes a molten state, and trimethylsilyl isocyanate and dibutyl tin dilaurate are released. At 120°C and under the catalytic action of dibutyl tin dilaurate as a catalyst, the trimethylsilyl isocyanate will chemically react with the polymethyl methacrylate in the shell and the amino bio-based itaconate-butadiene in the core at the same time. The present invention uses trimethylsilyl isocyanate as an intermediate bridge to strengthen the connection strength between the core and the shell, and effectively avoids the separation of the core and the shell under high temperature conditions.

[0117] With dibutyltin dilaurate as a catalyst, the reaction mechanism of trimethylsilyl isocyanate and polymethyl methacrylate at 120°C is as follows: During the reaction, the tin atom of dibutyltin dilaurate forms a coordination bond with the nitrogen atom of isocyanate, thereby activating the isocyanate group and making it easier to react. The isocyanate group (-NCO) of trimethylsilyl isocyanate is activated under the catalytic action of dibutyltin dilaurate, and the activated isocyanate group reacts chemically with the hydroxyl group (-OH) and amino group (-NH2) in polymethyl methacrylate to form a reaction site. As the reaction continues, the isocyanate group combines with the reaction site in polymethyl methacrylate to form a stable cross-linking structure.

[0118] The reaction mechanism of trimethylsilyl isocyanate and amino-based itaconate-butadiene rubber at 120°C with dibutyltin dilaurate as catalyst is as follows: amino-based itaconate-butadiene is a bio-based polymer compound containing amino groups (-NH2). As a nucleophilic reagent, the amino group (-NH2) is easy to react with the isocyanate group. As a nucleophilic reagent, the amino group (-NH2) attacks the electrophilic carbon atom of the isocyanate group (-NCO) to form an intermediate product. Under the action of the catalyst and a high temperature of 120°C, the intermediate product undergoes intramolecular rearrangement accompanied by elimination reactions, such as the elimination of the silyl group, to form a more stable carbamate compound structure.

[0119] In addition, dibutyltin dilaurate not only has a catalytic effect as a catalyst, but also can be used as a stabilizer for polyvinyl chloride, and can capture free radicals generated during the degradation of PVC to prevent the continuation of the chain reaction. In addition, under the action of the catalyst and high temperature, trimethylsilyl isocyanate reacts with unstable sites (such as double bonds, chlorine atoms, etc.) on the polyvinyl chloride chain to form stable chemical bonds, thereby further improving the stability of PVC. The polyvinyl chloride in the present invention serves as a carrier of the modifier, and under the action of dibutyltin dilaurate and trimethylsilyl isocyanate, the performance is stable and suitable for high temperature environments.

[0120] In summary, with dibutyltin dilaurate as a catalyst, at a temperature of 120°C, trimethylsilyl isocyanate, polymethyl methacrylate, and amino-modified bio-based itaconate-butadiene rubber can react chemically at the same time to generate a stable compound structure. Combined with the embedded connection between the modifier and the shell, the modifier can act as a bridge to strengthen the connection strength between the shell and the core at temperatures of 120°C and above.

[0121] Furthermore, the epoxy resin-specific halogen-free flame retardant is 9,10-dioxa-9,10-diaza-1,3,5,7-pentafluoro-2H-pyrrole-2-one.

[0122] Furthermore, the acid anhydride includes methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, the mass ratio of methyltetrahydrophthalic anhydride to methylhexahydrophthalic anhydride is 3:2, and the amount of acid anhydride added is 35% of the total mass of component A.

[0123] Furthermore, the coupling agent is coupling agent KH570 and coupling agent KH560, and the mass ratio of coupling agent KH570 to coupling agent KH560 is 1:1.

[0124] Furthermore, the component A also includes a leveling agent, a defoamer, and a dispersant for epoxy resin. The leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant. The added amount of the leveling agent, the defoamer, and the dispersant is 1.5% of the total mass of component A.

[0125] The method for preparing a lightweight flame-retardant epoxy casting material composition for capacitors comprises the following steps:

[0126] S1. Add filler and coupling agent to a vacuum mixer, treat at 80-85°C for 1.5-2.0 hours, then add epoxy resin, epoxy diluent, epoxy resin modifier, pigment and flame retardant to the vacuum mixer, then disperse at high speed at 85-90°C and -0.06--0.08MPa vacuum for 1.0-1.5 hours, filter the material to obtain component A;

[0127] S2. Add anhydride and accelerator into a reaction kettle, and stir at 75-85° C. for 1.0-2.0 hours to obtain component B;

[0128] S3. When in use, preheat components A and B to 70-80°C respectively, and then mix them evenly to obtain a lightweight flame-retardant epoxy casting material composition for capacitors. Example 1

[0129] A preferred embodiment of the present invention provides a lightweight flame retardant epoxy casting material composition for capacitors and a preparation method thereof.

[0130] The component A comprises the following components: epoxy resin, epoxy resin modifier, epoxy diluent, filler, pigment, flame retardant, coupling agent;

[0131] The component B includes the following components: a curing agent and an accelerator;

[0132] The epoxy resin includes bisphenol A epoxy resin E51 and bisphenol A epoxy resin E44, wherein the mass ratio of bisphenol A epoxy resin E51 to bisphenol A epoxy resin E44 is 1:1.5;

[0133] The epoxy diluent includes phenyl glycidyl ether and neopentyl glycol diglycidyl ether, the mass ratio of phenyl glycidyl ether to neopentyl glycol diglycidyl ether is 2:1, and the amount of epoxy diluent added is 18% of the total mass of the epoxy resin;

[0134] The filler comprises the following components: active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, thermal conductive aluminum oxide powder, and the density of the thermal conductive aluminum oxide powder is 3.3 g / cm 3, fineness is 800 mesh, density of hollow glass beads is 0.3g / cm 3 , hollow ceramic microspheres 0.8g / cm 3 ; The mass ratio of active silicon powder 1250 mesh, hollow glass beads, hollow coal slag powder, hollow ceramic microspheres, and thermal conductive aluminum oxide powder is 1:2:1:2:1, and the mass of the filler is 80% of the total mass of the epoxy resin;

[0135] The flame retardant is a halogen-free flame retardant for epoxy resin, the amount of the flame retardant added is 20% of the total mass of the epoxy resin, and the halogen-free flame retardant for epoxy resin is 9,10-dioxa-9,10-diaza-1,3,5,7-pentafluoro-2H-pyrrole-2-one;

[0136] The coupling agent is coupling agent KH570 and coupling agent KH560, the mass ratio of coupling agent KH570 and coupling agent KH560 is 1:1, and the amount of coupling agent added is 1.5% of the total mass of epoxy resin;

[0137] The curing agent is methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride in a mass ratio of 3:2, and the amount of anhydride added is 35% of the total mass of component A;

[0138] The accelerator is composed of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol, wherein the mass ratio of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol is 1:1:2:1:2, and the amount of the accelerator added is 1% of the mass of the curing agent;

[0139] The epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 25 parts of core-shell rubber particle modifier;

[0140] The core-shell rubber particle modifier comprises the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 40 parts of polyvinyl chloride;

[0141] The component A also includes a leveling agent, a defoamer, and a dispersant for epoxy resin. The leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant. The amount of the leveling agent, the defoamer, and the dispersant added is 1.5% of the total mass of component A, and the mass ratio of the leveling agent, the defoamer, and the dispersant is 1:1:1.

[0142] The method for preparing a lightweight flame-retardant epoxy casting material composition for capacitors comprises the following steps:

[0143] In this embodiment, the total mass of the epoxy resin is 100 kg, the mass of the bisphenol A epoxy resin E51 is 40 kg, and the mass of the bisphenol A epoxy resin E44 is 60 kg; the remaining components are added according to the above ratio;

[0144] S1. Add filler and coupling agent to a vacuum mixer, treat at 80-85°C for 1.5-2.0 hours, then add epoxy resin, epoxy diluent, epoxy resin modifier, pigment and flame retardant to the vacuum mixer, then disperse at high speed at 85-90°C and -0.06--0.08MPa vacuum for 1.0-1.5 hours, filter the material to obtain component A;

[0145] S2. Add anhydride and accelerator into a reaction kettle, and stir at 75-85° C. for 1.0-2.0 hours to obtain component B;

[0146] S3. When in use, preheat components A and B to 70-80°C respectively, and then mix them evenly to obtain a lightweight flame-retardant epoxy casting material composition for capacitors.

[0147] like Figure 1 As shown, Figure 1 This is an impact interface diagram of the cured lightweight flame-retardant epoxy castable of Example 1 under an impact force of 25KJ, and no fault or cracking occurs. Example 2

[0148] Based on Example 1, this embodiment is different from Example 1 in that the filler described in this embodiment includes the following components: active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, and thermally conductive alumina powder, wherein the thermally conductive alumina powder has a density of 3.0 g / cm3 and a fineness of 800 mesh, the hollow glass beads have a density of 0.3 g / cm3, and the hollow ceramic microbeads have a density of 0.8 g / cm3; wherein the mass ratio of active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, and thermally conductive alumina powder is 1:2:1:2:1, and the mass of the filler is 80% of the total mass of the epoxy resin. Example 3

[0149] Based on Example 1, this embodiment is different from Example 1 in that the filler described in this embodiment includes the following components: active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, and thermally conductive alumina powder, wherein the thermally conductive alumina powder has a density of 3.5 g / cm3 and a fineness of 800 mesh, the hollow glass beads have a density of 0.3 g / cm3, and the hollow ceramic microbeads have a density of 0.8 g / cm3; wherein the mass ratio of active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, and thermally conductive alumina powder is 1:2:1:2:1, and the mass of the filler is 80% of the total mass of the epoxy resin.

[0150] The density of thermal conductive alumina powder has the greatest impact on the density of the overall castable, while the density of other components is relatively low, within the error range of about ±0.2, and has little impact. Example 4

[0151] This embodiment is based on Embodiment 1, but is different from Embodiment 1 in that the amount of epoxy diluent added in this embodiment is 17% of the total mass of the epoxy resin. Example 5

[0152] This embodiment is based on Embodiment 1, but is different from Embodiment 1 in that the amount of epoxy diluent added in this embodiment is 17.5% of the total mass of the epoxy resin. Example 6

[0153] This embodiment is based on Embodiment 1, but is different from Embodiment 1 in that the amount of the accelerator added in this embodiment is 0.6% of the mass of the curing agent. Example 7

[0154] This embodiment is based on Embodiment 1, but is different from Embodiment 1 in that the amount of the accelerator added in this embodiment is 1.5% of the mass of the curing agent. Example 8

[0155] This embodiment is based on Embodiment 1, but differs from Embodiment 1 in that the epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 20 parts of core-shell rubber particle modifier, and the core-shell rubber particle modifier includes the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 40 parts of polyvinyl chloride. Example 9

[0156] This embodiment is based on Embodiment 1, but differs from Embodiment 1 in that the epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 30 parts of core-shell rubber particle modifier, and the core-shell rubber particle modifier includes the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 40 parts of polyvinyl chloride. Example 10

[0157] This embodiment is based on Embodiment 1, but differs from Embodiment 1 in that the epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 25 parts of core-shell rubber particle modifier, and the core-shell rubber particle modifier includes the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 50 parts of polyvinyl chloride. Embodiment 11

[0158] This embodiment is based on Embodiment 1, but differs from Embodiment 1 in that the epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 25 parts of core-shell rubber particle modifier, and the core-shell rubber particle modifier includes the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 45 parts of polyvinyl chloride. Example 12

[0159] This embodiment is based on the embodiment 1, but is different from the embodiment 1 in that the curing agent is methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride in a mass ratio of 3:2, and the amount of acid anhydride added is 30% of the total mass of component A. Embodiment 13

[0160] This embodiment is based on the embodiment 1, but is different from the embodiment 1 in that the curing agent is methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride in a mass ratio of 3:2, and the amount of acid anhydride added is 40% of the total mass of component A.

[0161] Comparative Example 1 is a method of the prior art, and the specific steps are as follows: 80 kg of hollow glass beads, 1.5 kg of coupling agents KH560 and KH570 are added to a kneader, and after treating at 80-90°C for 1.5 hours, 35 kg of bisphenol A epoxy resin E44, 50 kg of bisphenol A epoxy resin E51, 15 kg of epoxy diluent 678, and 15 kg of core-shell structure rubber particles CSR-2 are added, heated to 85 degrees and stirred for 1.5 hours, 1.5 kg of auxiliary agents, 1.5 kg of color paste, and 20 kg of flame retardant are added, and stirred evenly at high speed; the treated hollow glass beads and 40 kg of thermal conductive aluminum oxide are added, and dispersed evenly at high speed under vacuum conditions at 85°C to obtain a blue viscous liquid of component A, and the viscosity of component A at 75°C is 9000-9500 cps; 75 kg of methyl tetrahydroanhydride and Methyl hexahydroanhydride, 0.75kg of accelerator is added, reacted at 75°C for 1.5 hours, and the material is cooled to obtain component B, component B is a transparent viscous liquid with a viscosity of 60-120cp at 25°C; wherein the flame retardant is the same as the flame retardant described in Example 1, wherein the auxiliary agent includes a special leveling agent, a defoamer, and a dispersant for epoxy resin, the leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant, the amount of the leveling agent, the defoamer, and the dispersant is 1.5% of the total mass of component A, and the mass ratio of the leveling agent, the defoamer, and the dispersant is 1:1:1; components A and B are preheated to 70-80°C respectively, and then 100 parts by weight of component A and 35 parts by weight of component B are mixed and stirred evenly to obtain a lightweight flame retardant epoxy casting material composition for capacitors.

[0162] like Figure 2 As shown, Figure 2This is an impact interface diagram of the cured lightweight flame retardant epoxy castable of Example 1 under an impact force of 25KJ. Comparative Example 2

[0163] Comparative Example 2 is a method of the prior art, and the specific steps are as follows: 80 kg of hollow glass beads, 1.5 kg of coupling agents KH560 and KH570 are added to a kneader, and after treating at 80-90°C for 1.5 hours, 35 kg of bisphenol A epoxy resin E44, 50 kg of bisphenol A epoxy resin E51, 15 kg of epoxy diluent 678, and 20 kg of core-shell structure rubber particles CSR-2 are added, heated to 85°C and stirred for 1.5 hours, 1.5 kg of additives, 1.5 kg of color paste, and 20 kg of flame retardants are added, and stirred evenly at high speed; the treated hollow glass beads, 40 kg of thermal conductive aluminum oxide are added, and dispersed evenly at high speed under vacuum conditions at 85°C to obtain a blue viscous liquid of component A, and the viscosity of component A at 75°C is 9500-10000 cps; 75 kg of methyl tetrahydroanhydride and methyl Hexahydroanhydride, 0.75kg of accelerator are added, reacted at 75°C for 1.5 hours, and the material is cooled to obtain component B, component B is a transparent viscous liquid with a viscosity of 60-120cps at 25°C; wherein the flame retardant is the same as the flame retardant described in Example 1, wherein the auxiliary agent includes a leveling agent, a defoamer, and a dispersant for epoxy resin, the leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant, the amount of the leveling agent, the defoamer, and the dispersant is 1.5% of the total mass of component A, and the mass ratio of the leveling agent, the defoamer, and the dispersant is 1:1:1; components A and B are preheated to 70-80°C respectively, and then 100 parts by weight of component A and 35 parts by weight of component B are mixed and stirred evenly to obtain a lightweight flame retardant epoxy casting material composition for capacitors. Comparative Example 3

[0164] Comparative Example 3 is a method of the prior art, and the specific steps are as follows: 40 kg of hollow glass beads, 60 kg of hollow ceramic beads, and 1.5 kg of coupling agents KH560 and KH570 are added to a kneader, and after treating at 80-90°C for 1.5 hours, 35 kg of bisphenol A epoxy resin E44, 50 kg of bisphenol A epoxy resin E51, 15 kg of epoxy diluent 678, and 20 kg of core-shell structure rubber particles CSR-2 are added, heated to 85°C and stirred for 1.5 hours, and then auxiliary agents are added, all auxiliary agents totaling 1.5 kg, color paste 1.5 kg, flame retardant 20 kg, and stirred at high speed; the treated hollow glass beads and hollow ceramic beads, 20 kg of thermal conductive alumina are added, and dispersed evenly at high speed at 85°C under vacuum conditions to obtain component A, a blue viscous liquid, and component A has a viscosity of 7500-8500 cps at 75°C; 7 5kg methyl tetrahydroanhydride and methyl hexahydroanhydride, 0.75kg accelerator are added, reacted at 75°C for 1.5 hours, cooled and discharged to obtain component B, component B is a transparent viscous liquid with a viscosity of 60-120cps at 25°C. The flame retardant is the same as the flame retardant described in Example 1, wherein the auxiliary agent includes a special leveling agent, a defoamer, and a dispersant for epoxy resin, the leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant. The amount of the leveling agent, the defoamer, and the dispersant is 1.5% of the total mass of component A, and the mass ratio of the leveling agent, the defoamer, and the dispersant is 1:1:1; components A and B are preheated to 70-80°C respectively, and then 100 parts by weight of component A and 35 parts by weight of component B are mixed and stirred evenly to obtain a lightweight flame retardant epoxy casting material composition for capacitors. Comparative Example 4

[0165] Comparative Example 4 is a method of the prior art, and the specific steps are as follows: 80 kg of hollow glass beads are added to a kneader, and a total of 1.5 kg of coupling agents KH560 and KH570 are added. After treating at 80-90°C for 1.5 hours, 35 kg of bisphenol A epoxy resin E44, 50 kg of bisphenol A epoxy resin E51, 15 kg of epoxy diluent 678, and 25 kg of core-shell structure rubber particles CSR-2 are added. After heating to 85°C and stirring for 1.5 hours, 1.5 kg of auxiliary agents, 1.5 kg of color paste, and 20 kg of flame retardant are added, and the mixture is stirred at high speed and uniformly; the treated hollow glass beads and 40 kg of thermal conductive aluminum oxide are added, and the mixture is dispersed uniformly at high speed under vacuum conditions at 85°C to obtain component A, which is a blue viscous liquid. The viscosity of component A at 75°C is 10000-10500 cps. 75 kg of methyl tetrahydrofuran is weighed. anhydride and methyl hexahydroanhydride, add 0.75kg accelerator, react at 75℃ for 1.5 hours, cool and discharge to obtain component B, component B is a transparent viscous liquid with a viscosity of 60-120cps at 25℃; wherein the flame retardant is the same as the flame retardant described in Example 1, wherein the auxiliary agent includes a special leveling agent, a defoamer, and a dispersant for epoxy resin, the leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant, the amount of the leveling agent, the defoamer, and the dispersant is 1.5% of the total mass of component A, and the mass ratio of the leveling agent, the defoamer, and the dispersant is 1:1:1; preheat components A and B to 70-80℃ respectively, then take 100 parts by weight of component A and 35 parts by weight of component B and mix and stir evenly to obtain a lightweight flame retardant epoxy casting material composition for capacitors. Comparative Example 5

[0166] Comparative Example 5 is a method of the prior art, and the specific steps are as follows: 40 kg of hollow glass beads, 60 kg of hollow ceramic beads, 1.5 kg of coupling agents KH560 and KH570 are added to the kneader, and 35 kg of bisphenol A epoxy resin E44, 50 kg of bisphenol A epoxy resin E51, 15 kg of epoxy diluent 678, and 15 kg of core-shell structure rubber particles CSR-2 are added after treating at 85 ° C for 1.5 hours, and a total of 1.5 kg of additives and 1.5 kg of color paste are added. , 20kg of flame retardant, after high-speed stirring, add the treated hollow glass beads and hollow ceramic beads, 20kg of thermal conductive alumina, and disperse them evenly at high speed under vacuum conditions at 85℃ to obtain component A. Component A is a blue viscous liquid with a viscosity of 7500-8500cps at 75℃. Weigh 75kg of methyl tetrahydroanhydride and methyl hexahydroanhydride, add 0.75kg of accelerator, react at 75℃ for 1.5 hours, cool and discharge to obtain component B. Component B is a transparent viscous liquid with a viscosity of 60-120cps at 25℃. The flame retardant is the same as the flame retardant described in Example 1, and the auxiliary agent includes a special leveling agent, a defoamer, and a dispersant for epoxy resin. The leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant. The amount of the leveling agent, the defoamer, and the dispersant is 1.5% of the total mass of component A, and the mass ratio of the leveling agent, the defoamer, and the dispersant is 1:1:1; components A and B are preheated to 70-80° C. respectively, and then 100 parts by weight of component A and 35 parts by weight of component B are mixed and stirred evenly to obtain a lightweight flame-retardant epoxy casting material composition for capacitors. Comparative Example 6

[0167] This comparative example is based on Example 1. However, the difference between this comparative example and Example 1 is that the epoxy resin modifier in this comparative example is the core-shell structure rubber particles CSR-2, which are not modified. Comparative Example 7

[0168] This comparative example is based on Example 1. However, the difference between this comparative example and Example 1 is that the epoxy resin modifier in this comparative example is the core-shell structure rubber particles CSR-1, which are not modified. Comparative Example 8

[0169] This comparative example is based on Example 1. However, the difference between this comparative example and Example 1 is that in this comparative example, the core-shell structure rubber particle modifier is not used to modify the core-shell structure rubber particles, and the core-shell structure rubber particles are not subjected to pore-forming treatment. Comparative Example 9

[0170] This comparative example is based on Example 1. However, the difference between this comparative example and Example 1 is that in this comparative example, the core-shell structured rubber particles are not subjected to pore-forming treatment, and are directly subjected to modification treatment using a modifier.

[0171] Test Example 1

[0172] The lightweight flame-retardant epoxy casting material composition obtained in Examples 1-13 and Comparative Examples 1-9 was cured at 75°C for 5 hours, then at 90°C for 5 hours, and finally at 100°C for 5 hours to obtain a cured product, and the properties of the cured product were tested; the properties included hardness (Shore A), flexural strength (MPa), tensile strength (MPa), impact toughness (KJ / cm2), density (g / cm3), thermal conductivity (W / m / K), flame retardant grade, breakdown voltage (KV / mm), and hot and cold cycle test (-45°C~+120°C). The detection methods of the hardness (Shore A), flexural strength (MPa), tensile strength (MPa), impact toughness (KJ / cm2), density (g / cm3), thermal conductivity (W / m / K), flame retardant grade, breakdown voltage (KV / mm), and hot and cold cycle test (-45°C~+120°C) of the cured product are prior art and will not be elaborated on in detail. The performance test results are shown in Table 1 and Table 2.

[0173] Table 1 Test results of the properties of the cured products in Examples 1-13

[0174] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Hardness (Shore A) 95.6 94.3 95.4 93.7 94.1 93.8 94.7 94.9 95.5 93.9 94.3 93.2 95.1 Bending strength (MPa) 145 140 142 139 141 137 144 143 143 140 141 137 142 Tensile strength (MPa) 89 83 84 81 83 79 88 88 88 82 84 78 85 Impact toughness (KJ / cm2) 25.1 24.5 24.7 24.3 24.5 24.1 25.0 25.1 25.1 24.1 24.2 23.7 24.7 Density(g / cm3) 1.032 1.030 1.033 1.034 1.034 1.033 1.035 1.033 1.033 1.034 1.031 1.032 1.034 Thermal conductivity (W / m / K) 0.58 0.52 0.55 0.49 0.51 0.52 0.54 0.53 0.52 0.51 0.54 050 0.49 Flame retardant grade UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 Breakdown voltage (KV / mm) 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 Hot and cold cycle test (-45℃-+120℃) 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking 100 cycles without cracking

[0175] Table 2 Test results of the properties of the cured products of Comparative Examples 1-9

[0176] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Hardness (Shore A) 90.8 91.2 92.1 91.1 92.2 90.8 90.9 91.2 91.4 Bending strength (MPa) 125 129 135 124 117 128 130 116 120 Tensile strength (MPa) 73 74 76 75 72 74 74 71 73 Impact toughness (KJ / cm2) 18.7 22.3 22.7 23.2 22.1 22.2 22.3 18.2 18.7 Density(g / cm3) 1.087 1.076 1.113 1.104 1.113 1.032 1.033 1.035 1.031 Thermal conductivity (W / m / K) 0.54 0.52 0.55 0.49 0.51 0.56 0.54 0.47 0.49 Flame retardant grade UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 UL-0 Breakdown voltage (KV / mm) 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 18~23 Hot and cold cycle test (-45℃-+120℃) 25 cycles without cracking 40 cycles without cracking 40 cycles without cracking 40 cycles without cracking 40 cycles without cracking 40 cycles without cracking 40 cycles without cracking 40 cycles without cracking 40 cycles without cracking

[0177] Combining Table 1 and Table 2, it can be seen that the ratios of the components are different, and the performances achieved are different. Example 1 of the present invention is the best ratio. The comprehensive performance of the epoxy castable of the present invention is better than the comprehensive performance of the epoxy castable of the prior art.

[0178] Test Example 2

[0179] The core-shell rubber particles CSR-1, CSR-2, and the core-shell rubber particles in Example 1, Examples 8-11, Comparative Example 8, and Comparative Example 9 were placed in an environment of 120°C, 150°C, 180°C, and 200°C to observe whether the core and shell of the core-shell rubber particles were separated. The test results are shown in Table 3. The core-shell rubber particles in Example 1 and Examples 8-11 are modified core-shell rubber particles.

[0180] Table 3 Temperature resistance test of core-shell structure rubber particles

[0181] Example 1 Example 8 Example 9 Example 10 Embodiment 11 Comparative Example 8 Comparative Example 9 Core-shell structure rubber particles CSR-1 Core-shell structure rubber particles CSR-2 120℃ No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell 150℃ No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell Core-shell separation No separation of core and shell Core-shell separation Core-shell separation 180℃ No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell No separation of core and shell Core-shell separation Core-shell separation Core-shell separation Core-shell separation 200℃ No separation of core and shell Core-shell separation No separation of core and shell Core-shell separation Core-shell separation Core-shell separation Core-shell separation Core-shell separation Core-shell separation

[0182] From the data in Table 3, it can be seen that the temperature resistance of the modified core-shell rubber particles in the present invention can reach above 180°C, and can reach up to 200°C, which solves the problem that the temperature resistance of the existing core-shell rubber particles is low and can only reach up to 120°C. Figure 1 , Figure 2 It can be seen that Figure 1 There is no obvious cross section. Figure 2 The present invention has strong impact resistance.

[0183] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A lightweight flame retardant epoxy casting material composition for capacitors, characterized in that: Comprising component A and component B; The component A comprises the following components: epoxy resin, epoxy resin modifier, epoxy diluent, filler, pigment, flame retardant, coupling agent; The component B includes the following components: a curing agent and an accelerator; The epoxy resin includes bisphenol A epoxy resin E51 and bisphenol A epoxy resin E44, wherein the mass ratio of bisphenol A epoxy resin E51 to bisphenol A epoxy resin E44 is 1:1.5; The epoxy diluent includes phenyl glycidyl ether and neopentyl glycol diglycidyl ether, the mass ratio of phenyl glycidyl ether to neopentyl glycol diglycidyl ether is 2:1, and the amount of epoxy diluent added is 17-18% of the total mass of the epoxy resin; The filler comprises the following components: active silicon micropowder 1250 mesh, hollow glass beads, hollow coal slag micropowder, hollow ceramic microbeads, thermal conductive aluminum oxide powder, and the density of the thermal conductive aluminum oxide powder is 3.0-3.5g / cm 3 , fineness is 800 mesh, density of hollow glass beads is 0.2-0.3g / cm 3 , hollow ceramic microspheres 0.75-0.90g / cm 3 ; The mass ratio of active silicon powder 1250 mesh, hollow glass beads, hollow coal slag powder, hollow ceramic microspheres, and thermal conductive aluminum oxide powder is 1:2:1:2:1, and the mass of the filler is 80% of the total mass of the epoxy resin; The flame retardant is a halogen-free flame retardant specially used for epoxy resin, and the amount of the flame retardant added is 20% of the total mass of the epoxy resin; The coupling agent is one or more of coupling agent KH570, coupling agent KH560, and titanate coupling agent, and the amount of the coupling agent added is 1.5% of the total mass of the epoxy resin; The curing agent is anhydride, and the amount of anhydride added is 30%-40% of the total mass of component A; The accelerator is composed of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol, wherein the mass ratio of triphenylphosphine, 2-methyl-4-ethylimidazole, benzyldimethylamine, triphenylphosphine, and 2,4,6-tris(dimethylaminomethyl)phenol is 1:1:2:1:2, and the amount of the accelerator added is 0.6%-1.5% of the mass of the curing agent; The epoxy resin modifier is a toughening modifier; The epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 20-30 parts of core-shell rubber particle modifier; The shell of the core-shell rubber particle is a polymethyl methacrylate shell with uniformly distributed pores, and the core of the core-shell rubber particle is an amino-based bio-based itaconate-butadiene rubber; The core-shell rubber particle modifier comprises the following components in parts by weight: 20-30 parts of dibutyltin dilaurate, 80-90 parts of trimethylsilyl isocyanate, 10-15 parts of nano-activated carbon, and 40-50 parts of polyvinyl chloride.

2. A lightweight flame retardant epoxy casting material composition for capacitors according to claim 1, characterized in that: The core-shell rubber particle modifier comprises the following components in parts by weight: 30 parts of dibutyltin dilaurate, 90 parts of trimethylsilyl isocyanate, 15 parts of nano-activated carbon, and 40 parts of polyvinyl chloride; The epoxy resin modifier is composed of 100 parts of core-shell rubber particles and 25 parts of core-shell rubber particle modifier.

3. A lightweight flame retardant epoxy casting material composition for capacitors according to claim 1, characterized in that: The epoxy resin modifier is prepared by the following method: A. Preparation of core-shell rubber particle modifier The core-shell rubber particle modifier is prepared by the following method: polyvinyl chloride is molten in a container at 100° C., trimethylsilyl isocyanate and nano-activated carbon are added to the polyvinyl chloride, and the mixture is stirred uniformly at 100° C. to obtain a glue solution, and dibutyltin dilaurate is added to the glue solution after the mixture is cooled to 40-50° C., and the mixture is stirred uniformly to obtain a shell rubber particle modifier; Preparation of core-shell rubber particles The preparation method of the core-shell rubber particles comprises the following steps: B1. Kernel Preparation Bio-based itaconate is prepared from bio-based monomers itaconic acid and isopentanol by esterification reaction, and then by emulsion polymerization, a vinyl-containing silane modifier, deionized water, bio-based itaconate, butadiene and a redox initiator are mixed at 60-80°C in an inert atmosphere to form an emulsion; then, the bio-based itaconate is copolymerized with butadiene in the emulsion state to generate bio-based itaconate-butadiene rubber, wherein the mass ratio of bio-based itaconate to butadiene is 3:2, the copolymerization temperature is 75-85°C, and the reaction time is 7-8 hours; the generated bio-based itaconate-butadiene rubber is subjected to an amination reaction with an amination agent to obtain an amination bio-based itaconate-butadiene rubber; B2. Shell Preparation The invention adopts an emulsion polymerization method, uses ammonium persulfate as an initiator, and OP-10 as an emulsifier, and at 70° C., methyl methacrylate is mixed with ammonium persulfate, OP-10, and deionized water for emulsion polymerization to obtain a PMMA latex particle solution; N,N-dimethylformamide is added to the PMMA latex particle solution, and the mixed solution is fully stirred under ultrasonic wave to ensure that N,N-dimethylformamide is uniformly dispersed in the PMMA latex particles, so as to obtain a mixed solution containing PMMA latex particles; and the mixed solution containing the PMMA latex particles is placed at room temperature, and N,N-dimethylformamide is naturally volatilized. As the solvent is volatilized, the solvent in the PMMA latex particles is removed to form a pore structure, so as to obtain polymethyl methacrylate latex particles with uniformly distributed pores; B3. Core-shell structure formation The prepared aminated bio-based itaconate-butadiene rubber particles are used as seed particles and dispersed in a suitable solvent to form a stable seed particle dispersion; polymethyl methacrylate latex particles with uniform pores are mixed with the seed latex particle dispersion to ensure that the two particles are fully in contact, and then azobisisobutyronitrile is added to carry out a grafting reaction between the polymethyl methacrylate latex particles with uniform pores and the aminated bio-based itaconate-butadiene rubber particles at 80-100° C. After the grafting reaction is completed, the product is separated, washed and dried to obtain aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure, wherein the aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure are core-shell rubber particles; Modification of core-shell rubber particles A shell rubber particle modifier is sprayed onto the core-shell rubber particles with a high-pressure spray gun. The shell rubber particle modifier penetrates into the pores of the outer shell of the core-shell rubber particles under the action of high pressure. Part of the shell rubber particle modifier is filled in the pores of the outer shell of the core-shell rubber particles. Part of the shell rubber particle modifier acts on the inner core through the pores of the outer shell of the core-shell rubber particles to complete the modification of the core-shell rubber particles, thereby obtaining shell rubber particles modified by the core-shell rubber particle modifier, wherein the modified shell rubber particles are epoxy resin modifiers.

4. A lightweight flame retardant epoxy casting material composition for capacitors according to claim 1, characterized in that: The special halogen-free flame retardant for epoxy resin is 9,10-dioxa-9,10-diaza-1,3,5,7-pentafluoro-2H-pyrrole-2-one.

5. A lightweight flame retardant epoxy casting material composition for capacitors according to claim 1, characterized in that: The acid anhydride includes methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, the mass ratio of methyltetrahydrophthalic anhydride to methylhexahydrophthalic anhydride is 3:2, and the amount of acid anhydride added is 35% of the total mass of component A.

6. A lightweight flame retardant epoxy casting material composition for capacitors according to claim 1, characterized in that: The coupling agents are coupling agent KH570 and coupling agent KH560, and the mass ratio of coupling agent KH570 to coupling agent KH560 is 1:

1.

7. A lightweight flame retardant epoxy casting material composition for capacitors according to claim 1, characterized in that: The component A also includes a leveling agent, a defoamer and a dispersant for epoxy resin. The leveling agent is Rh-t1084 leveling agent, the defoamer is BYK-A530 defoamer, and the dispersant is a polyether active amine copolymer dispersant. The amount of the leveling agent, the defoamer and the dispersant added is 1.5% of the total mass of component A.

8. A method for preparing a lightweight flame retardant epoxy casting composition for capacitors according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Add filler and coupling agent to a vacuum mixer, treat at 80-85° C. for 1.5-2.0 hours, then add epoxy resin, epoxy diluent, epoxy resin modifier, pigment and flame retardant to the vacuum mixer, then disperse at high speed at 85-90° C. and -0.06- -0.08 MPa vacuum for 1.0-1.5 hours, filter the material to obtain component A; S2. Add anhydride and accelerator into a reaction kettle, and stir at 75-85° C. for 1.0-2.0 hours to obtain component B; S3. When in use, preheat components A and B to 70-80°C respectively, and then mix them evenly to obtain a lightweight flame-retardant epoxy casting material composition for capacitors.

9. The method for preparing a lightweight flame retardant epoxy casting material composition for capacitors according to claim 8, characterized in that: The epoxy resin modifier in step S1 is prepared by the following method: A. Preparation of core-shell rubber particle modifier The core-shell rubber particle modifier is prepared by the following method: polyvinyl chloride is molten in a container at 100° C., trimethylsilyl isocyanate and nano-activated carbon are added to the polyvinyl chloride, and the mixture is stirred uniformly at 100° C. to obtain a glue solution, and dibutyltin dilaurate is added to the glue solution after the mixture is cooled to 40-50° C., and the mixture is stirred uniformly to obtain a shell rubber particle modifier; B. Preparation of core-shell rubber particles The preparation method of the core-shell rubber particles comprises the following steps: B1. Kernel Preparation Bio-based itaconate is prepared from bio-based monomers itaconic acid and isopentanol by esterification reaction, and then by emulsion polymerization, a vinyl-containing silane modifier, deionized water, bio-based itaconate, butadiene and a redox initiator are mixed at 60-80°C in an inert atmosphere to form an emulsion; then, the bio-based itaconate is copolymerized with butadiene in the emulsion state to generate bio-based itaconate-butadiene rubber, wherein the mass ratio of bio-based itaconate to butadiene is 3:2, the copolymerization temperature is 75-85°C, and the reaction time is 7-8 hours; the generated bio-based itaconate-butadiene rubber is subjected to an amination reaction with an amination agent to obtain an amination bio-based itaconate-butadiene rubber; B2. Shell Preparation The invention adopts an emulsion polymerization method, uses ammonium persulfate as an initiator, and OP-10 as an emulsifier, and at 70° C., methyl methacrylate is mixed with ammonium persulfate, OP-10, and deionized water for emulsion polymerization to obtain a PMMA latex particle solution; N,N-dimethylformamide is added to the PMMA latex particle solution, and the mixed solution is fully stirred under ultrasonic wave to ensure that N,N-dimethylformamide is uniformly dispersed in the PMMA latex particles, so as to obtain a mixed solution containing PMMA latex particles; and the mixed solution containing the PMMA latex particles is placed at room temperature, and N,N-dimethylformamide is naturally volatilized. As the solvent is volatilized, the solvent in the PMMA latex particles is removed to form a pore structure, so as to obtain polymethyl methacrylate latex particles with uniformly distributed pores; B3. Core-shell structure formation The prepared aminated bio-based itaconate-butadiene rubber particles are used as seed particles and dispersed in a suitable solvent to form a stable seed particle dispersion; polymethyl methacrylate latex particles with uniform pores are mixed with the seed latex particle dispersion to ensure that the two particles are fully in contact, and then azobisisobutyronitrile is added to carry out a grafting reaction between the polymethyl methacrylate latex particles with uniform pores and the aminated bio-based itaconate-butadiene rubber particles at 80-100° C. After the grafting reaction is completed, the product is separated, washed and dried to obtain aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure, wherein the aminated bio-based itaconate-butadiene rubber / PMMA composite particles with a core-shell structure are core-shell rubber particles; C. Modification of core-shell rubber particles A shell rubber particle modifier is sprayed onto the core-shell rubber particles with a high-pressure spray gun. The shell rubber particle modifier penetrates into the pores of the outer shell of the core-shell rubber particles under the action of high pressure. Part of the shell rubber particle modifier is filled in the pores of the outer shell of the core-shell rubber particles. Part of the shell rubber particle modifier acts on the inner core through the pores of the outer shell of the core-shell rubber particles to complete the modification of the core-shell rubber particles, thereby obtaining shell rubber particles modified by the core-shell rubber particle modifier, wherein the modified shell rubber particles are epoxy resin modifiers.

Citation Information

Patent Citations

  • Epoxy castable composition for power capacitor and preparation method of epoxy castable composition

    CN118006085A

  • Lightweight epoxy castable composition and preparation method thereof

    CN116855037A